Challenges and adaptation strategies for Riesling grape (Vitis vinifera L) production in the southwest desert in the USA - Naznin, Most Tahera; Azad, Md Obyedul Kalam; Moe, Jill (Frontiers in Plant Science, 2025)
Riesling, a traditionally cool-climate grape variety, faces increasing challenges when cultivated in the Desert Southwest region of the United States, where extreme heat, water scarcity, and nutrient-poor soils prevail. This paper reviews published research data to identify the key stress factors affecting Riesling production in these arid environments and explores adaptation strategies to enhance its viability. This paper synthesizes potential strategies for adapting Riesling cultivation to desert environments under increasing climate variability. These strategies include high-elevation planting, the use of drought-tolerant rootstocks (e.g., Ramsey, 1616C, 110R, 1103P, 140Ru), and canopy or trellising systems to mitigate thermal stress and optimize microclimates. Soil health improvements through mulching, composting, cover cropping, and biochar amendments are also reviewed for their roles in enhancing water retention and nutrient cycling. Smart irrigation technologies utilizing IoT-based soil moisture sensors and AI-driven scheduling are discussed as tools for maximizing water efficiency. Additional innovations, such as climate modeling, remote sensing for vineyard management, and agrivoltaic systems, are explored for their potential contributions to sustainable vineyard design and operation. Through this literature review, it appears that Riesling production could adapt to desert climates by integrating traditional practices with precision agriculture and sustainability-driven innovations. While these strategies show promise in supporting fruit quality and long-term resilience, however, further applied research is needed to validate their effectiveness in specific arid contexts.